TEACHERS’ TECHNOLOGICAL CAPABILITY AND CAREER DEVELOPMENT - D. Deloviar, JR, Reynaldo; B. Vasquez, Michael; D. De Sale, Leonor (IDEAS: Journal of Management & Technology, 2024)
Proficiency in technology is crucial for career advancement, enhancing effectiveness, fostering innovation, and preparing educators for digital-age demands. This study investigated the relationship between Technological Capability and Career Development among 267 secondary teachers in Roxas City Division, focusing on digital literacy, pedagogical integration, peer collaboration, professional growth, continuous learning, and career exploration. The research explored variations in technological capability and career development based on teachers' age, sex, educational attainment, and length of service. In the quest to bridge age-related disparities in technological capabilities among educators and address the transformative impact of technology on career trajectories, this research addressed  the under-explored relationship between technology capability and career development among educators in the constructs of  DepEd Roxas City Division seeking to establish a connection between Information and Communications Technology (ICT) skills and career development, aiming elevate educators' career prospects in this evolving educational landscape. The study utilized a quantitative descriptive correlational research design in which data were collected through a researcher-made questionnaire and analyzed using IBM SPSS Statistics version 26, employing various statistical methods such as frequency, mean, t-test, f-test, and Pearson’s correlation. Results revealed an Excellently Manifested level of technological capability and career development in the Schools Division, with significant differences observed based on sex, age, and length of service. No significant differences were found based on educational attainment. The study highlighted the significant relationship between teachers' technological capability and career development, emphasizing the influence of demographic factors. It suggests that educational institutions and policymakers can leverage these findings to enhance professional growth strategies, ensuring teachers are well-equipped to navigate the evolving educational landscapes in the digital era.